Encounter in English as a Second or Foreign Language Classroom (Journal of NELTA, 2011)
This article discusses how mother-tongue interference can influence second or forreign language learning, specifically learning English. In Nepal not only does the mother tongue interfere with English learning, but also the methods used in the schools, specifically the grammar translation method and the deductive approach to teaching grammar, influence student learning as well.Key words: Tertiary level; Inductive approach; Deductive approach; Fossilization; Language transferJournal of NELTAVol. 15 No. 1-2 December 2010Page: 109-109Uploaded date: 4 May, 2011DOI: 10.3126/nelta.v15i1-2.4615